From memory to cultural heritage: reflection on ex-votos as a social testimony (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT The present article is reserved for the presentation of the ex-voto, object placed, through the act of relief, in catholic sanctuaries, in specific, in the rooms of miracles, as element of the cultural patrimony. Here, a cut of the productions of the Ex-votos of Brazil and Ex-votos of Mexico Projects, fomented by the CNPq, that incursed in almost a hundred miracle halls in Brazil and in Mexico. The miracle halls are spaces of cultural heritage that bring, among their riches, the nature of ex-votos, objects that testify to the faith and that present histories of lives, portraits in pictorial, photographic supports, tickets, sculptures, organic objects and objects industrialized representative of collective and individual situations, true sources of information that bring local, regional and national histories, true vectors of social memory and cultural and religious heritage. KEY-WORDS Ex-voto; Document; Social memory; Cultural patrimony.